Quantitative MRI texture analysis of the lateral pterygoid muscle in unilateral temporomandibular joint disorders - Tao Huang; Shu-Fan Zhao; Zhi-Qiang Song; Zhong-Cheng Gong (Head & Face Medicine)
Abstract Background This study utilized MRI-based texture analysis to quantify structural alterations in the lateral pterygoid muscle (LPM) among MR images with unilateral anterior disc displacement (uADD) of the temporomandibular joint. Retrospective analysis of anonymized MR images from 232 uADD patients and 123 healthy individuals (January 2022– December 2024), approved by the Ethics Committee of Wenzhou Medical University Affiliated School of Stomatology (Ethics Number: WYKQ 2024008) with waived informed consent due to the use of de-identified retrospective data, was conducted to identify diagnostic markers and possible related pathological changes of disc displacement. According to the inclusion and exclusion criteria four groups of MR images were included in this study: the healthy temporomandibular joints (H-TMJ) of individuals with uADD, joints with anterior disc displacement with reduction (ADDwR), joints with anterior disc displacement without reduction (ADDwoR), and MR images from normal volunteers as the healthy group (HG). Four texture parameters were used for analysis: the angular second moment (ASM), Contrast, inverse difference moment (IDM) and Entropy. Results Statistically significant differences (P < 0.05) were found between groups for the ASM, Contrast, IDM, and Entropy variables, indicating their potential as diagnostic markers. Additionally, Entropy values differed significantly between the ADDwoR and ADDwR groups (P < 0.05), highlighting its diagnostic potential in distinguishing these two conditions. The severity of ADD disease showed varying degrees of correlation with specific texture parameters, with significant associations observed for ASM, Contrast, IDM, and Entropy (P < 0.05). Conclusions The texture parameters of the LPM exhibit significant changes in MR images with anterior disc displacement(ADD). Notably, the Entropy value of the LPM demonstrates high diagnostic utility in distinguishing ADDwoR from ADDwR, particularly in cases of complex disc displacement involving deformation or remodeling. Furthermore, the severity of ADD disease shows varying degrees of correlation with specific texture parameters. However, further research is required to validate the relationship between numerical texture changes in the LPM and their corresponding pathological alterations. Clinical trial number Not applicable.